Ten years-experience of sunitinib in the treatment of advanced pan-NETs: an update on safety profile. Issue 3 (4th March 2022) - Vivanet, G.; Gervaso, L.; Laffi, A.; Rubino, M.; Spada, F.; Fazio, N.
ABSTRACT: Introduction: Sunitinib still represents a milestone in the treatment for progressive, well-differentiated, advanced panNETs. Areas covered: We performed an evidence reappraisal to critically discuss its safety profile. We included nine studies, five clinical trials and four real-world (RW) studies. Within non-real-world (NRW) studies, diarrhea was the most frequent clinical AE. With regard to G3-4 AEs, fatigue and hypertension were the two most frequent, while neutropenia was the most recurrent hematological one. Considering four real-world trials, hand-foot-syndrome (HFS) was the most frequent clinical any-grade AE of any grade and neutropenia was the most common G3-4. Alongside to the AEs rate, the discontinuation rate of sunitinib due to TRAEs was variable among all the nine selected studies, ranging from 10% to 35% in the NRW setting and from 7% to 31% in the RW setting. Conversely, temporary interruption is an accepted strategy to reduce toxicity, even though not specifically tested in pan-NET. Expert opinion: Till now, sunitinib continues to be one of the main therapeutic options for patients with well differentiated advanced panNETs, potentially covering any line of treatment. Therefore, tolerability plays a crucial role to increase adherence to therapy and maximize QoL.